Implementation of Guided Imagery Techniques for Adolescents Experiencing Dysmenorrhea - Waode Erty Hikma; Mustikawati Mustikawati; Morika Wahdini; Silvia Silvia (GLOBAL HEALTH SCIENCE GROUP, 2023)
Menstruation is a natural cycle in women characterized by the release of blood through the vagina. Menstrual pain or dysmenorrhea often causes a throbbing sensation, cramps in the lower abdomen, and pain that can spread to the back and inner thighs. Deep breathing relaxation techniques are an effective method for reducing pain by relieving muscle tension, reducing anxiety, and preventing the spread of pain stimuli. This study aims to analyze the effectiveness of deep breathing relaxation techniques in reducing menstrual pain in women with dysmenorrhea. The research method uses a descriptive case study approach involving two clients who were given deep breathing relaxation techniques as an intervention. The research subjects were 80 female adolescents in the Meilia Medika Health Vocational School area. Sampling was done using purposive sampling technique and only 2 participants were taken. Data was analyzed descriptively. The results showed that in the first client, before the relaxation technique was performed, the pain scale felt was 6/10. After the application of the relaxation technique, the pain decreased to 3/10 and on the second to fifth day it dropped to 1/10. On the sixth and seventh days, the pain was no longer felt. The second client initially experienced pain on a scale of 9/10, which decreased to 5/10 after the application of the relaxation technique. On the second to fourth day, the pain scale decreased to 2/10, and on the sixth to seventh day the pain was no longer felt. The conclusion of this study is that deep breathing relaxation techniques are proven to be effective in reducing the scale of menstrual pain if done correctly according to the Standard Operating Procedure (SOP). Both clients stated that this method helped reduce menstrual pain significantly.